Theoretical Study of Adenine to Guanine Transition Assisted by Water and Formic Acid Using Steered Molecular Dynamic Simulations - Tolosa, Santiago; Sansón, Jorge A.; Hidalgo, Antonio (Frontiers in Chemistry, 2019)
The free energy profiles of the adenine to guanine conversion in the gas and aqueous phases were obtained by applying steered molecular dynamic (SMD) simulations. Three processes were considered to explain the mechanism assisted by water and formic acid molecules. The first process is hydrolytic deamination of adenine, then oxidation with formic acid of the hypoxanthine previously formed, and finally, the animation from xanthine to guanine. None of the simulated processes were both thermodynamically and kinetically favourable. The result, considering all processes involved, leads us to conclude that the A G conversion is not spontaneous and that the lifetimes of guanine formed in this conversion allows us to say that it could participate in genetic mutations Although lower activation and reaction energies for the conversion is observed in gas phase, the effect of the medium can influence the mechanism that is followed depending on whether there are molecules surrounding the system that hinder or favour the transfers, as happens for the deamination (more exergonic in solution) or oxidation and amination (more endergonic in solution) processes. Transition states that describe nucleophilic attacks present high barriers, being the highest the one that describes the break between the base and the formic acid and the formation of a formaldehyde molecule. The protonation of amino and imino nitrogen are the only exergonic steps in all simulations. On the other hand, the attack of the water molecules on the base is the most endergonic step of the conversion. We also want to highlight the importance of performing SMD simulations to investigate the reaction mechanisms of complex systems in solution at a molecular level. Simulations allow analysis of the evolution of processes along the reaction coordinates, which provides information about transition and intermediate structures and thermodynamic and kinetic properties through energy profiles.